Was Kierkegaard Inspired by Medieval Mysticism? Meister Eckhart’s »Abgeschiedenheit« and Kierkegaard’s »Udsondring« - Florin, Frits (KIERKEGAARDIANA, 2002)
Was Kierkegaard Inspired by Medieval Mysticism? Meister Eckhart’s »Abgeschiedenheit« and Kierkegaard’s »Udsondring«